2019
DOI: 10.1111/bjh.15838
|View full text |Cite
|
Sign up to set email alerts
|

PET‐adapted therapy after three cycles of ABVD for all stages of Hodgkin lymphoma: results of the GATLA LH‐05 trial

Abstract: Summary The role of Ann Arbor staging in determining treatment intensity after achieving a negative positron emission tomography (PET) has not been established in classical Hodgkin lymphoma (cHL). Patients with stage I–IV cHL, received three cycles of ABVD (doxorubicin, bleomycin, vinblastine, dacarbazine) and an interim PET scan (PET3). PET3‐negative patients received no further therapy. PET3‐positive patients received three additional cycles of ABVD plus involved‐field radiation therapy or salvage chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…When comparing the results of LH-05 with our previous clinical trial (LH-96) (17) there was no difference in EFS and OS at 5 years but in LH-05 only 31% received more than 3 cycles of ABVD and IFRT compared to 61% and 100% in LH-96, thus demonstrating that an iPET adapted approach reduces exposure to chemo and radiotherapy without compromising the long-term treatment outcome.…”
Section: Interim Pet/ct Adapted Clinical Trials For Hodgkin Lymphoma In Argentinamentioning
confidence: 75%
See 2 more Smart Citations
“…When comparing the results of LH-05 with our previous clinical trial (LH-96) (17) there was no difference in EFS and OS at 5 years but in LH-05 only 31% received more than 3 cycles of ABVD and IFRT compared to 61% and 100% in LH-96, thus demonstrating that an iPET adapted approach reduces exposure to chemo and radiotherapy without compromising the long-term treatment outcome.…”
Section: Interim Pet/ct Adapted Clinical Trials For Hodgkin Lymphoma In Argentinamentioning
confidence: 75%
“…601 HL patients were enrolled: 316 had stage III-IV and 285 were favorable patients, 60 (15%) of this latter (15%) were slow-responders. The 5-years event-free survival (EFS) of patients entering CR after 3 cycles of ABVD in the favorable group was significantly higher (89%) with respect to the slow responders (66%) and to the advanced-stage group (72%; P < .001) treated with 6 ABVD courses +/-IFRT (17).…”
Section: Interim Pet/ct Adapted Clinical Trials For Hodgkin Lymphoma In Argentinamentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical significance of fluorine-18-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography/computed tomography (PET/CT) in the diagnosis or management of lymphoma is gradually becoming important 1 , 2 . Although it remains controversial, several previous studies reported that the interim PET/CT response could predict long-term clinical outcomes in cases of Hodgkin lymphoma (HL), aggressive non-Hodgkin lymphoma (NHL), and follicular lymphoma 3 5 . However, the role of 18 F-FDG PET/CT assessment in indolent lymphomas other than follicular lymphoma is unclear due to variable 18 F-FDG avidity 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Although it remains controversial, several previous studies reported that the interim PET/CT response could predict long-term clinical outcomes in cases of Hodgkin lymphoma (HL), aggressive non-Hodgkin lymphoma (NHL), and follicular lymphoma [3][4][5] . However, the role of 18 F-FDG PET/CT assessment in indolent lymphomas other than follicular lymphoma is unclear due to variable 18 F-FDG avidity 6 .…”
mentioning
confidence: 99%